Lateral medullary syndrome: an unwanted ischemia to identify early - Prajjwal, Priyadarshi; Inban, Pugazhendi; Nagre, Abhijit; Shah, Mujtaba Hussain; Chaudhary, Ansh; Ranjan, Raunak; Chaudhary, Bhupendra (International Journal of Advances in Medicine, 2022)
Lateral medullary syndrome also referred to as Wallenberg syndrome, posterior inferior cerebellar artery (PICA) syndrome, or vertebral artery syndrome is a cluster of neurological symptoms and signs brought on by obstructions in the blood vessels supplying the medulla, which causes ischemia or infarction of the brainstem. The vertebral artery or the posterior inferior cerebellar artery are the arteries most frequently affected with lateral medullary syndrome. The most prevalent symptom is transient ischemic attack (TIA) with dizziness or vertigo and atherosclerosis in the posterior cerebral circulation being the most common cause. Lateral Medullary Syndrome patients suffer from strokes or infarction and also present with vomiting, nausea, gait impairment, instability, hoarseness, and swallowing difficulties. Depending on the particular nuclei and fibers involved, different indications will appear. CT/MRI imaging is used to diagnose conditions. The majority of management is supportive, including risk factor reduction for additional ischemia events as well as speech and occupational therapy following an acute intervention. In this review article, we discuss the etiopathogenesis and factors leading to lateral medullary syndrome along with a comprehensive discussion on its clinical features, challenges in diagnosis, and treatment.